Aerobic exercise and unripe grape extract as antioxidant do not protect the kidney against cisplatin induced nephrotoxicity - Sayyedehnikta Kasae; Saeid Keshavarz; Bahar Mazaheri; Behzad Zolfaghari; Ardeshir Talebi; Mehdi Nematbakhsh (Society of Diabetic Nephropathy Prevention, 2019)
Background: Nephrotoxicity is the cisplatin therapy side effect due to stress oxidative formation and lack of antioxidants. Objectives: The role of aerobic exercise and three different doses of unripe grape extract as an antioxidant on cisplatin-induced nephrotoxicity were studied Materials and Method: Seventy male Wistar rats were randomly divided into groups of control, cisplatin (2.5 mg/kg/d for 7 days), aerobic exercise + cisplatin and unripe grape extract and also aerobic exercise + unripe grape extract. Aerobic exercise was administered in period of 7 weeks (5 days/week, 1 h/d), and unripe grape extract was used in three different doses of 20, 100, 200 mg/ kg/d for period of 7 weeks. Results: Cisplatin elevated the serum levels of blood urea nitrogen (BUN), creatinine and malondialdehyde (MDA), and also kidney weight and kidney tissue damage score and decreased body weight and the kidney tissue levels of nitrite significantly (P<0.05), but aerobic exercise or unripe grape extract did not alter the parameters toward normal levels. Conclusions: Based on these findings, aerobic exercise and antioxidant such as unripe grape extract may not protect the kidney against cisplatin-induced nephrotoxicity during anti-cancer therapy